Thymol alleviates silica dioxide nanoparticle-induced reproductive performance toxicity via antioxidant and anti-inflammatory mechanisms in male rats - Mahmoud A. Khedr; Amira A. Goma; Rashed R. Rashed; Hossam G. Tohamy; Mustafa Shukry; Sara E. El-Kazaz (Scientific Reports)
Abstract Nanoparticles (NPs) have gained increasing attention due to their unique physicochemical properties and broad applications. However, concerns about their potential toxicity, particularly reproductive toxicity, have emerged. Silica dioxide nanoparticles (SiO₂-NPs) are among the most commonly used NPs and have been linked to adverse effects on male reproductive health. This study aimed to evaluate the potential ameliorative effect of thymol, a natural monoterpene phenol with antioxidant and anti-inflammatory properties, against SiO₂-NPs-induced reproductive toxicity in male rats. Twenty-four adult male Sprague-Dawley rats were randomly assigned to four groups: control, SiO₂-NPs-treated (10 mg/kg body weight, intraperitoneally), thymol-treated (30 mg/kg body weight, orally), and SiO₂-NPs + thymol co-treated. Treatments were administered daily for 56 days. Male reproductive performance was evaluated through sexual behavior assessment, sperm characteristics, reproductive hormone levels, oxidative stress markers, inflammatory biomarkers, gene expression analysis, and histopathological examination of testicular tissue. Results revealed that SiO₂-NPs significantly impaired reproductive performance, indicated by reduced sperm motility, viability, and count, along with increased sperm abnormalities. Thymol co-administration significantly restored testosterone levels and partially normalized elevated LH and FSH levels caused by SiO₂-NPs, indicating endocrine protection. Moreover, SiO₂-NPs induced oxidative stress, elevated pro-inflammatory cytokines (TNF-α and IL-6), and disrupted the expression of key genes associated with oxidative stress response (NRF2), apoptosis (BAX, BCL-2), steroidogenesis (STAR, CYP11A1), and spermatogenesis (PRM1, GATA4). Thymol co-administration with SiO₂-NPs significantly mitigated these adverse effects by restoring antioxidant levels, reducing inflammation, and improving gene expression and the histological architecture of the testes. The findings suggest that thymol has a promising protective role against SiO₂-NPs-induced male reproductive toxicity through its antioxidant and anti-inflammatory actions.